Comparative performance of prognostics for remaining useful life of bearing. (November 2020) - Nistane, Vinod M
The frequent failure components in rotary machinery are the rolling element bearings as it is important for prognostics of rolling element bearings. In this study, the data-driven technique was used to develop the prognostic models based on particle swarm optimization techniques. These models apply to estimate the rolling element bearing degradation and predict remaining useful life. Initially, the fault features were extracted by processing the vibration signals through wavelet packet decomposition based on the intensifying impulsive characteristics and superiority of features. Health indicators evaluate from fault features. The prognostic models are developed with the following approaches: Gated recurrent neural network, classification and regression tree, and Autoregressive-Moving Average models. Performances of models are verified on the basis of error in prediction. To verify the suggested methodology, an experiment on normal and faulty bearings was conducted using a bearing test rig. Experimental results clarify that the prognostic algorithms predict bearing remaining useful life with significant robustness. Outperformance of the proposed method and conformation of degree of accuracy from results indicate that remaining useful life is conjectured as inference compared with the published literature.